Preparation, characterization and tribological properties of ultrathin MoS2 nanosheets. (3rd November 2017) - Zhang, Xianghua; Xue, Yaping; Ye, Xia; Xu, Hongxiang; Xue, Maoquan
Abstract: In this work, ultrathin MoS2 nanosheets were prepared via a solid-state reaction route. The structure and morphology of the obtained samples were characterized by x-ray diffraction, transmission electron microscopy and scanning electron microscopy. The influences of the reaction durations and raw materials molar ratio on the sizes and morphologies of the MoS2 nanostructures were discussed. And according to the experimental results, a formation mechanism of the ultrathin MoS2 nanosheets was proposed. The tribological behaviors of the synthesized MoS2 samples as additives in paraffin oil were determined on an UMT-2 tribometer. The experimental results indicated that the obtained samples possessed great anti-friction and anti-wear properties as lubrication additive in paraffin oil.